2013
DOI: 10.1021/nl4023435
|View full text |Cite
|
Sign up to set email alerts
|

Interface Magnetism in Epitaxial BiFeO3-La0.7Sr0.3MnO3 Heterostructures Integrated on Si(100)

Abstract: We report on the heteroepitaxial growth of ferroelectric (FE)-antiferromagnetic (AFM) BiFeO3 (BFO) on ferromagnetic La0.7Sr0.3MnO3 (LSMO), integrated on Si(100) using pulsed laser deposition via the domain matching epitaxy paradigm. The BFO/LSMO films were epitaxially grown on Si(100) by introducing epitaxial layers of SrTiO3/MgO/TiN. X-ray diffraction, scanning electron microscopy, high-resolution transmission electron microscopy, X-ray photo absorption spectroscopy, and atomic force microscopy were employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 21 publications
5
32
1
Order By: Relevance
“…The study of interface magnetic coupling in bilayers involving manganites with other layers has been widely reported in the past. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Similar enhancement in switching field (7309 Oe) was observed [19] when the SRO layer is interfaced with the ferroelectric and antiferromagnetic BiFeO 3 layers. It should be noted that these switching field values are much higher than the values observed for individual layers.…”
Section: Functional Oxides Research Lettersupporting
confidence: 55%
“…The study of interface magnetic coupling in bilayers involving manganites with other layers has been widely reported in the past. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Similar enhancement in switching field (7309 Oe) was observed [19] when the SRO layer is interfaced with the ferroelectric and antiferromagnetic BiFeO 3 layers. It should be noted that these switching field values are much higher than the values observed for individual layers.…”
Section: Functional Oxides Research Lettersupporting
confidence: 55%
“…However, using a TiN, MgO and STO buffer layer based on the DME paradigm, 18,19 the authors have demonstrated that multi-layer oxide heterostructures can be successfully deposited on Si(100). [23][24][25] The samples studied here were BFO/LSMO/STO/MgO/TiN/Si(100), LSMO/STO/MgO/TiN/Si(100) and BFO/STO/MgO/TiN/Si(100), which were labelled as samples A, B and C, respectively. Si (004) Intensity: a.u.…”
Section: 21mentioning
confidence: 99%
“…Essentially, the hysteresis loop shifts along the negative field axis as shown in inset of Fig. 1 heterostructures [21]. Observed positive exchange bias can be explained on the basis of the competing exchange interaction between the FM -AFM phases and the coupling between an applied magnetic field -and spins which are aligned antiferromagnetically at the surface [4].…”
Section: Resultsmentioning
confidence: 87%
“…A plethora of experimental investigations have proved that negative magnetic field cooling (NFC) would have pronounced effects on exchange bias properties [21][22][23]. Such marked results pertinent to exchange bias have been attributed to existence of pinned and rotatable spins at the interfaces.…”
mentioning
confidence: 99%